Google Form or Quizizz, which is Better? - Zahra Nurusshofa; Endin Nokik Stujanna; Martiem Mawi; Rizka Aries Putranti; Wasis Sumartono; Sigid Edy Purwanto; Wawang S Sukarya; Rizki Edmi Edison (STKIP Yapis Dompu, 2023)
Conventional face-to-face learning has always been used as the primary teaching method, including in medical studies. With large-scale social restrictions enforced due to the COVID-19 pandemic, the medical education system needs to be able to optimize remote learning, while maintaining its target achievement to produce high-quality medical students. The shift in learning methods is accompanied by a change to remote testing methods. Google Forms and Quizizz are two platforms that are often used as a method for remote testing. However, the two platforms have not yet been compared in relation to medical student outcomes. This study uses a semi-quantitative approach. Sources of data utilized in the study are the topical test scores and the grades of 20 semester-two UHAMKA medical students. The students utilized remote learning methods, with testing conducted via Quizizz and Google Forms. Using distance learning, there was a significant difference in the topical tests scores when students used Quizizz as a method of testing, compared to when using Google Forms (paired t test, p=0,002). The majority of students preferred to use Google Forms as a testing method (90%) than Quizizz (10%). In conclusion, as a testing method, Google Forms showed higher learning outcome scores than Quizizz.